2023
DOI: 10.1001/jamanetworkopen.2023.25658
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian Dietary Patterns and Cardiometabolic Risk in People With or at High Risk of Cardiovascular Disease

Tian Wang,
Cynthia M. Kroeger,
Sophie Cassidy
et al.

Abstract: IMPORTANCEPlant-based diets are known to improve cardiometabolic risk in the general population, but their effects on people at high risk of cardiovascular diseases (CVDs) remain inconclusive.OBJECTIVETo assess the association of vegetarian diets with major cardiometabolic risk factors, including low-density lipoprotein cholesterol (LDL-C), hemoglobin A1c (HbA1c), systolic blood pressure (SBP), and body weight in people with or at high risk of CVDs.DATA SOURCESThis meta-analysis was registered before the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Non-HDL-C, TC and LDL-C concentrations were significantly higher in the RMEs compared to vegans. Metaanalysis of twenty RCTs showed that consuming a vegetarian (including vegan) dietary pattern was associated with a 0.4 mmol/L reduction in LDL-C compared to RMEs [47]. Another meta-analysis of 30 RCTs illustrated that the vegetarian (including vegan) dietary pattern is associated with reduced TC (−0.34 mmol/L) and LDL-C (−0.30 mmol/L) compared with RMEs [48].…”
Section: Discussionmentioning
confidence: 99%
“…Non-HDL-C, TC and LDL-C concentrations were significantly higher in the RMEs compared to vegans. Metaanalysis of twenty RCTs showed that consuming a vegetarian (including vegan) dietary pattern was associated with a 0.4 mmol/L reduction in LDL-C compared to RMEs [47]. Another meta-analysis of 30 RCTs illustrated that the vegetarian (including vegan) dietary pattern is associated with reduced TC (−0.34 mmol/L) and LDL-C (−0.30 mmol/L) compared with RMEs [48].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis on the vegetarian diet found that consuming a vegetarian diet was associated with significant improvements in low-density lipoprotein cholesterol (LDL-C), glycated hemoglobin (HbA1c), and body weight beyond the standard therapy in individuals at high risk of CVDs. However, the changes in LDL-C and HbA1c did not reach the clinical significance as per the cutoff target [74]. Few studies have been conducted on the effects of a vegetarian diet on cardiovascular risk in primary prevention.…”
Section: Stress During Pregnancy and Its Relationship With Foodmentioning
confidence: 93%
“…Papamichou et al (2019), reported reduction in HbA1c levels from adherence to vegetarian and Mediterranean dietary patterns on type 2 diabetes prevention and treatment [52]. Wang et al (2023) [53] found higher improvements in HbA1c levels from vegetarian diets compared to actual and conventional energy-restricted diets related to diabetes [53]. Moreover, a systematic review by Toumpanakis et al (2018) [51] on adults with type 2 diabetes found PBDs significantly improved HbA1c levels when compared to dietary guidelines for diabetes.…”
Section: Plant-based Diet Effect On Blood Glucose and Type 2 Diabetes...mentioning
confidence: 99%